PENGARUH MOTIVASI DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN DI PT. HONG TANG ASIA - Andoko, Natasya Sekar Ayuningtyas; Siahaan, Matdio; Anas, Haryudi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research aims to determine how the relation between the variables of Motivation (X1) and Career Development (X2) affects the Employee Performance (Y) variable at PT. Hong Tang Asia. The research data was obtained through a questionnaire distributed to the employees of PT. Hong Tang Asia. The population in this research consists of 120 employees of PT. Hong Tang Asia, resulting in a sample size of 120 employees, with data analysis conducted using SEM-PLS (Structural Equation Modeling-Partial Least Squares) and processed using SmartPLS4 software. The findings from the study indicate that: 1) Motivation significantly affects Employee Performance, 2) Career Development significantly affects Employee Performance, and 3) Motivation and Career Development significantly affect Employee Performance simultaneously.